2023
DOI: 10.1037/dev0001582
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of psychopathic traits dimensions on the development of indirect aggression from childhood to adolescence.

Abstract: Children who show elevated levels of indirect aggression (IA) from childhood to adolescence are at increased risks of experiencing detrimental outcomes. Some studies suggest that psychopathic traits could act as a predisposing vulnerability in the development of IA, but the contributions of all three dimensions of psychopathic traits in explaining developmental trajectories of IA from childhood to adolescence remain unclear. This study aimed to determine if the three dimensions of psychopathic traits during ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Moreover, Zych, Ttofi, et al, (2019) found that perpetration of school bullying was positively related to CU traits (OR = 2.55), and Graziano and Garcia (2016) reported that youths with ADHD were high in CU traits (d = .68), even after accounting for conduct problems and emotion recognition/understanding (aspects of cognitive empathy). CU traits also have been positively related to children's indirect aggression, although CU traits did not predict trajectories of indirect aggression when the latter was simultaneously predicted by conduct problems and the other aspects of psychopathy (Boutin et al, 2023).…”
Section: Empirical Relations Of Empathy-related Responding To Externa...mentioning
confidence: 89%
“…Moreover, Zych, Ttofi, et al, (2019) found that perpetration of school bullying was positively related to CU traits (OR = 2.55), and Graziano and Garcia (2016) reported that youths with ADHD were high in CU traits (d = .68), even after accounting for conduct problems and emotion recognition/understanding (aspects of cognitive empathy). CU traits also have been positively related to children's indirect aggression, although CU traits did not predict trajectories of indirect aggression when the latter was simultaneously predicted by conduct problems and the other aspects of psychopathy (Boutin et al, 2023).…”
Section: Empirical Relations Of Empathy-related Responding To Externa...mentioning
confidence: 89%